Antioxidant Action of Mangrove Polyphenols against Gastric Damage Induced by Absolute Ethanol and Ischemia-Reperfusion in the Rat - de-Faria, Felipe Meira; Alves Almeida, Ana Cristina; Luiz-Ferreira, Anderson; Takayama, Christiane; Dunder, Ricardo Jose; da Silva, Marcelo Aparecido [UNESP]; Salvador, Marcos Jose; Abdelnur, Patricia Verardi; Eberlin, Marcos Nogueira; Vilegas, Wagner [UNESP]; Toma, Walber; Monteiro Souza-Brito, Alba Regina (Hindawi Publishing Corporation, 2012)
Rhizophora mangle, the red mangrove, has long been known as a traditional medicine. Its bark has been used as astringent, antiseptic, hemostatic, with antifungic and antiulcerogenic properties. In this paper, we aimed to evaluate the antioxidant properties of a buthanolic fraction of the R. mangle bark extract (RM) against experimental gastric ulcer in rats. Unib-Wh rats received pretreatment of R. mangle after the induction of gastric injury with absolute ethanol and ischemia-reperfusion. Gastric tissues from both methods were prepared to the enzymatic assays, the levels of sulfhydril compounds (GSH), lipid peroxides (LPO), and the activities of glutathione reductase (GR), glutathione peroxidase (GPx), superoxide dismutase (SOD) and myeloperoxidase (MPO) were measured. The RM protected the gastric mucosa in both methods used, ethanol-induced gastric ulcer and ischemia-reperfusion, probably, by modulating the activities of the enzymes SOD, GPx, and GR and increasing or maintaining the levels of GSH; in adittion, LPO levels were reduced. The results suggest that the RM antioxidant activity leads to tissue protection; thus one of the antiulcer mechanisms present on the pharmacological effects of R. mangle is the antioxidant property.